2016
DOI: 10.1123/jpah.2015-0664
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time and Occupational Physical Activity in Early and Late Adulthood in Relation to Later Life Physical Functioning

Abstract: This study highlights the importance of LTPA on later life functioning, but also indicates the inverse effects that may be caused by heavy manual work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Both of these studies, however, did not focus on older adults specifically. Time doing leisure activities was also associated with lower risks of having limitations in ADL, which is in accordance with previous research [16,53]. The results emphasize the importance of active leisure for health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both of these studies, however, did not focus on older adults specifically. Time doing leisure activities was also associated with lower risks of having limitations in ADL, which is in accordance with previous research [16,53]. The results emphasize the importance of active leisure for health.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it lowers the risk for all-cause, cardio-vascular disease-related, and cancer-related mortality, even in older adults, who did not increase leisure time PA until late adulthood [ 15 ]. Higher levels of leisure time PA earlier in life are positively associated with better physical functioning in older age [ 16 ]. Being physically active at work has positive effects on health [ 11 , 17 , 18 ], however these associations are not sufficiently researched for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…From a health promotion perspective, it can therefore be concluded that simply increasing the apprentices' volume of PA (even more) is probably not an effective strategy for promoting the health of this target group. The so-called PA paradox assumes that the amount of PA within the occupational context is even likely to exert a detrimental influence on workers' health [35][36][37][38]. A recent article discussed that too low intensities, too long activity durations, insufficient recovery times, inadequate postures, and a low activity control may lead to this negative effect [39].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to biomechanical factors at work was also associated with low walking speed, with significant trends in risks across ordered categories of exposure duration for all the three factors examined in both men and women. In several studies, walking speed was found inversely associated with exposure to workplace ergonomic factors or intense physical work, in contrast with LPTA, which instead has been reported to have a protective effect (27,30,32,43), partly due to increased muscle strength (44). The opposite direction of the association with ergonomic factors at work, compared with LTPA, may be due, as discussed in the Introduction, to differences in type, frequency, and duration of the physical activity performed, which in the case of occupational physical activity is characterized mainly by static effort and constrained postures for long periods without sufficient pauses and recovery (30), features which may overload joint, tendon, and muscle structures, increasing the risk of developing musculoskeletal disorders (45,46); these, in turn, would increase the likelihood of functional disability (47).…”
Section: Discussionmentioning
confidence: 96%
“…Exposure to some occupational ergonomic factors also seems to reduce walking speed at an older age. Previous heavy manual work was associated with lower gait speed in one study (27), whereas in another study, manual longest-held occupation during lifetime was associated with reduced performance using the Short Physical Performance Battery test, which includes walking speed, together with the chair stand test and the balance test (28). Two other studies found opposite effects of longterm occupational and leisure-time physical activity (LTPA) during midlife on self-reported mobility during old age, with the former associated with an increased risk and the latter with a decreased risk of poor physical functioning (29,30).…”
Section: Introductionmentioning
confidence: 92%